Is it necessary for clinical tumor volume including neck muscles in target volume delineation of nasopharyngeal carcinoma?. Issue 6 (5th November 2021) - Chen, Fei; Kong, Xiangquan; Wu, Haixia; Fang, Weining; Fei, Zhaodong; Wu, Zhupeng; Zhao, Dan; Ma, Liqin
Abstract: Objectives: To calculate the shrinkage of the neck muscles and dosimetric changes and to clarify the necessity of covering part of the muscle in neck node region delineation for patients with nasopharyngeal carcinoma (NPC) treated with intensity‐modulated radiotherapy. Methods: In total, 44 patients with NPC were enrolled. Distances between the lateral border of the neck muscles and longitudinal midline were measured on every selected slice. This process was repeated three times, and the mean values of the three distances of planning computed tomography (CT) images and repeated CT images were adopted (labeled d 1 and d 2). The mean value of the differences between d 1 and d 2 was regarded as the medial shrinkage of the neck muscles. The initial clinical target volume of cervical lymph nodes (CTV‐n) was shifted medially with the value of shrinkage, yielding a new CTV‐n. Doses that covered 95% of the planning tumor volume (PTV) (D95), 99% of the PTV (D99), mean dose (Dmean), and maximum dose (Dmax) were used to calculate the dosimetric variation between the initial and new CTV‐n. Comparisons were performed using the paired samples t test. Results: The median d 1 was 3.81 cm (range: 1.19‐8.20 cm), and the median d 2 was 3.68 cm (range: 0.94‐9.59 cm), with a statistically significant difference ( P < .001). The mean difference between d 1 and d 2 was 1.5 ± 3.1 mm ( SD ). The D95 and D99 of PTV of initial CTV‐n decreased by 0.38% and 0.62% ( P < .001 and P < .001, respectively). Conclusion: Patients with NPC experienced medial shrinkage of the neck muscles by 1.5 mm, and the consequent dose variation was negligible. It is unnecessary to cover part of the muscles in the delineation of the CTV‐n.